COLLECTION OF NON TAX STATE REVENUE (NON-TAX) IN THE SALE OF LAND BY LAW NO. 9 OF 2018 IN THE OFFICE OF NATIONAL LAND AGENCY SEMARANG CITY - Kirana Asmitha Dewi; Maryanto Maryanto (Jurnal Akta, 2019)
The purpose of this study was to: 1) To determine the form of non-tax state revenues (non-tax) in the transfer of land rights under Act No. 9 in 2018 at the National Land Agency of Semarang. 2) To determine the barriers and solutions in implementing the collection of non-tax state revenues (non-tax) in the National Land Agency of Semarang In the transition of land rights. The data used this research is primary data, secondary data, and data that can support tertiary study, which is then analyzed by the method of empirical juridical approach in this research means is that in analyzing the problems made by combining the ingredients of the law (which is a secondary data) with the primary data collected in the field is about voting Non Tax Revenue Office Bada National Land Semarang city. This approach is implemented by conducting direct research of the respondents and narasumbr in the field with the aim to collect objective data, which is referred to as primary data.Based on the results of data analysis concluded that: 1)Lodging Tax State Revenue for the transfer-usually collected through intermediaries Deed Official Land (PPAT), although the edges remain submitted to the National Land Agency, and it could have been through a formula or a look of Value Zone Land is there, but at the time of calculation Land Deed official typically does not have any land value zone or commonly called Zoning Value of Land, it is estimated only through the ground's Value Zone only. Because all for the sake of security clien to avoid underpayment. And with the Non Tax Revenue This brings several benefits to the State, the institutions and the community itself. 2) With the non-tax state revenue has not run optimally, so there must be some rules and systems are modified so that it runs with optimal collection.Keywords: Non Tax Revenue; Transfer of Rights to Land; Buy and sell.